Shaping the water conditions in the postmining areas (a case-study of Brown Coal Mine "Adamów") = Kształtowanie stosunków wodnych na obszarach górniczych (na przykładzie Kopalni Węgla Brunatnego "Adamów") - Fagiewicz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the issues of shaping the water conditions in the mining areas given the example of Brown Coal Mine "Adamów". At the stage of the exploitation of deposit by opencast mining, the water conditions in the mining areas are transformed, which is associated with the need to adapt their functions to the needs of the mining and energy sectors.
Keywords: obszary pogórnicze; warunki wodne; odzyskiwanie wody; post-mining areas; water conditions; water reclamation